Changes in Free Amino Acid Concentration in Rye Grain in Response to Nitrogen and Sulfur Availability, and Expression Analysis of Genes Involved in Asparagine Metabolism - Postles, Jennifer; Curtis, Tanya Y.; Powers, Stephen J.; Elmore, J. S.; Mottram, Donald S.; Halford, Nigel G. (Frontiers in Plant Science, 2016)
Free asparagine plays a central role in nitrogen storage and transport in many plant species due to its relatively high ratio of nitrogen to carbon. However, it is also a precursor for acrylamide, a Class 2a carcinogen that forms during high-temperature processing and cooking. The concentration of free asparagine was shown to increase by approximately 70 % in rye grain in response to severe sulfur deficiency (F-test, p = 0.004), while the concentration of both free asparagine and free glutamine increased (by almost three-fold and approximately 62 %, respectively) in response to nitrogen application (F-test, p < 0.001 for free asparagine; p = 0.004 for free glutamine). There were also effects of nutrient supply on other free amino acids: The concentration of free proline, for example, showed a significant (F-test, p = 0.019) effect of nitrogen interacting with sulfur, with the highest concentration occurring when the plants were deprived of both nitrogen and sulfur. Polymerase chain reaction products for several genes involved in asparagine metabolism and its regulation were amplified from rye grain cDNA. These genes were asparagine synthetase-1 (ScASN1), glutamine synthetase-1 (ScGS1), potassium-dependent asparaginase (ScASP), aspartate kinase (ScASK), and general control non-derepressible-2 (ScGCN2). The expression of these genes and of a previously-described sucrose nonfermenting-1-related protein kinase-1 gene (ScSnRK1) was analysed in flag leaf and developing grain in response to nitrogen and sulfur supply, revealing a significant (F-test, p < 0.05) effect of nitrogen supply on ScGS1 expression in the grain at 21 days post-anthesis. There was also evidence of an effect of sulfur deficiency on ScASN1 gene expression. However, although this effect was large (almost 10-fold) it was only marginally statistically significant (F-test, 0.05 < p < 0.10). The study reinforced the conclusion that nutrient availability can have a profound impact on the concentrations of different free amino acids, something that is often overlooked by plant physiologists but which has important implications for flavor, color and aroma development during cooking and processing, as well as the production of undesirable contaminants such as acrylamide.